Synergizing human resources and management accounting in managing flexible work arrangement: a balanced scorecard model / Sharifah Rahama Amirul ... [et al.] - Amirul, Sharifah Rahama; Amirul, Sharifah Milda; Mail, Rasid; Justine@Abdul Aziz, Jainurin; Dasan, Jakaria (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The ongoing industrial revolution of the modern workplace, driven by changing societal and technological trends, has necessitated a shift towards flexible working arrangements (FWAs). This transformation has gained momentum in the post-pandemic era, rendering traditional work practices increasingly impractical in the foreseeable future of business. Consequently, business leaders must develop strategic plans to assess their organisations’ readiness for transitioning to more flexible or hybrid work environments. To address this need, our study aims to develop a balanced scorecard (BSC) hybrid model that fosters strategic collaboration between human resources (HR) and management accounting (MA). Drawing upon our findings, we propose a reimagined role for HR and MA, centered around a hybrid model that incorporates concepts from the balanced scorecard (BSC). This innovative hybrid model creates value and readiness for businesses seeking to adapt to the future by embracing FWAs. Our model not only facilitates the implementation of FWAs, emphasizing their importance beyond the immediate challenges of the past, but also underscores their potential to enhance overall business performance and sustainability.